MENANAMKAN BUDAYA SADAR LINGKUNGAN DI SEKOLAH DASAR: PEMANFAATAN SAMPAH ORGANIK SEBAGAI PEMBELAJARAN PRAKTIS - Rosita Dewi, Khristi; Ika Metalin, Ari; Subrata, Heru (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe how the implementation of instilling an environmentally conscious culture at Sekolah Dasar Negeri  Wage 2 Taman. This research uses a qualitative approach with descriptive research. The research was conducted at Sekolah Dasar Negeri  Wage 2 Taman with the research subjects being the principal, 2 teachers, 4 students, 1 janitor, and parents of students. Data were collected through interview, observation and documentation techniques. Data analysis was carried out through 3 stages, namely data reduction, data presentation and conclusion drawing. Data validity was tested using source triangulation and technique triangulation. The results showed that environmentally conscious culture is implemented through 3 steps, namely planning, implementation and evaluation. Planning activities are forming a school environmental management team, making environmental studies and planning environmental actions. Activities carried out during implementation are making environmentally sound policies, implementing environment-based curriculum, conducting participatory-based environmental activities, and managing environmentally friendly supporting facilities. The success of the implementation is evaluated by monitoring the state of biodiversity in the school, and monitoring students' ability to manage the environment from cognitive, affective and psychomotor aspects. Supporting factors that influence the implementation of an environmentally friendly school culture are the location of the school. While the inhibiting factor is that there are still students who lack awareness in sorting waste and there is still a lot of waste at school that has not been put in the trash according to the category of organic or inorganic waste.   Keywords: elementary school, environmentally conscious culture, organic waste